Lairds, land and sustainability : Scottish perspectives on upland management - Glass, Jayne; Price, Martin F.; Warren, Charles; Scott, Alister (Edinburgh : Edinburgh University Press, 2013)
Scotland is at the heart of modern, sustainable upland management. Large estates cover vast areas of the uplands, with a long, complex and emotive history of ownership and use. In recent decades, the Scottish uplands have increasingly been the arena for passionate debates over large-scale land management issues. Crucially, what kinds of ownership and management will best deliver sustainable futures for upland environments and communities? Although the globally unique dominance of private ownership remains a distinctive characteristic of Scotland's uplands, increasing numbers of estates are now.
pt. 1. Sustainability in the uplands -- pt. 2. Perspectives from private landownership -- pt. 3. Perspectives from community and NGO landownership -- pt. 4. Aligning upland estate management with sustainability.
boek
Keywords: Land use, Rural -- Scotland; Uplands -- Scotland -- Management; Land use, Rural -- Environmental aspects -- Scotland; Sustainable development -- Scotland